2018
DOI: 10.1002/jat.3722
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microRNA expressions for the identification of chemical hazards in in vivo and in vitro hepatic injury models

Abstract: Biofluid‐based biomarkers provide an efficient tool for hazard identification of chemicals. Here, we explored the potential of microRNAs (miRNAs) as biomarkers for hepatotoxicity of chemicals by linking in vitro to in vivo animal models. A search of the literature identified candidate circulating miRNA biomarkers of chemical‐induced hepatotoxicity. The expression of candidate miRNAs (miR‐122, miR‐151a, miR‐192, miR‐193a, miR‐194, miR‐21, miR‐29c), was determined by real‐time reverse transcription‐polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In line with our results, Xue et al [46] found elevated miR-93 in the circulation of HCC patients, although not evaluated in combination with AFP and DCP. On the other hand, to the best of our knowledge, miR-151a has not been associated with HCC, but with toxic liver damage and obesity [47,48], and other diseases like atopic dermatitis [49] and glioblastoma [50].…”
Section: Discussionmentioning
confidence: 84%
“…In line with our results, Xue et al [46] found elevated miR-93 in the circulation of HCC patients, although not evaluated in combination with AFP and DCP. On the other hand, to the best of our knowledge, miR-151a has not been associated with HCC, but with toxic liver damage and obesity [47,48], and other diseases like atopic dermatitis [49] and glioblastoma [50].…”
Section: Discussionmentioning
confidence: 84%
“…MicroRNAs (miRNAs) are short, non-coding RNAs of approximately 22 nucleotides in length that regulate gene expression by selectively binding to the 3ʹ untranslated regions of messenger RNAs (mRNAs), thereby inhibiting translation or degrading the transcript [1,2]. Recently there has been great enthusiasm for using miRNAs as biofluid-based biomarkers of diseases and toxicity [3][4][5][6][7][8][9]. miRNAs are highly sequence conserved across mammalian species and some are stable in extracellular environments upon release from cells, either by active transport or passively through membrane leakage [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs can be released from cells into biofluids, including blood, urine, cerebrospinal fluid and saliva [20]. MicroRNAs are stable and readily detectable in biofluids, and numerous studies have reported that their levels in biofluids reflect changes at the tissue level of several organs, including liver, kidney, heart and brain [10,[21][22][23][24].…”
mentioning
confidence: 99%